2020
DOI: 10.1111/1759-7714.13352
|View full text |Cite
|
Sign up to set email alerts
|

Utility of CT radiomics for prediction of PD‐L1 expression in advanced lung adenocarcinomas

Abstract: Background We aimed to assess if quantitative radiomic features can predict programmed death ligand 1 (PD‐L1) expression in advanced stage lung adenocarcinoma. Methods This retrospective study included 153 patients who had advanced stage (>IIIA by TNM classification) lung adenocarcinoma with pretreatment thin section computed tomography (CT) images and PD‐L1 expression test results in their pathology reports. Clinicopathological data were collected from electronic medical records. Visual analysis and radiomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 47 publications
(109 reference statements)
2
58
1
Order By: Relevance
“…48 Jiang et al reported that PET/CT radiomics features could be used to assess PD-L1 expression levels in NSCLC, 21 and a similar conclusion was confirmed by Yoon et al in patients with lung adenocarcinoma. 22 Our results demonstrated that radiomics-based features were superior to conventional clinical models in identifying PD-L1 expression, but the mechanism of the relationship between radiomics and underlying driving biology must be validated.…”
Section: Dovepressmentioning
confidence: 79%
See 2 more Smart Citations
“…48 Jiang et al reported that PET/CT radiomics features could be used to assess PD-L1 expression levels in NSCLC, 21 and a similar conclusion was confirmed by Yoon et al in patients with lung adenocarcinoma. 22 Our results demonstrated that radiomics-based features were superior to conventional clinical models in identifying PD-L1 expression, but the mechanism of the relationship between radiomics and underlying driving biology must be validated.…”
Section: Dovepressmentioning
confidence: 79%
“…Cases with PD-L1-stained cells ranging from 1% to 10% of the total tumor cells were considered PD-L1positive in pancreatic cancer, 36 and Yoon et al applied CT radiomics for predicting PD-L1 expression and defined PD-L1 positive as ≥50% (TPS) with any intensity in NSCLC. 22 Some research ignored the intensity of staining to a certain extent, which influenced on the PD-L1 predictive accuracy and response to immunotherapy. Consequently, standard evaluation criteria and accurate cut-off values are urgently needed in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown that the radiomic analysis can be used to predict the mutation status of several oncogenes (16,17). Currently, most studies in lung cancer have been done in primary tumors using computed tomography (CT) images (18)(19)(20)(21)(22). For example, Gevaert et al used CT images-based signature of primary lung tumors to predict EGFR mutation status (23).…”
Section: Introductionmentioning
confidence: 99%
“…Although monotherapy with PD-1 or PD-L1 drugs is usually well tolerated, the combination treatment increases the risk of immune-related adverse events [8]. So, biomarkers with predictive role need to be developed to augment patient bene t, diminish the risk of toxicity, and guide the combination approaches [9,10]. Although the expression of PD-L1 on tumor cells positivity improves the clinical bene t population, PD-L1 detection alone is not satisfactory for patient selection and e cacy prediction in most malignancies [11].…”
mentioning
confidence: 99%